The techniques of artistic gymnastics as gender technologies: the educational experience of female gymnasts (PerCursos, 2025)
The presented article emerges from research conducted in the Master's Program in Physical Education (ISEF, Universidad de la República) between 2021 and 2022. Of an autoethnographic nature, the study was based on 14 months of fieldwork in a gymnasium in the city of Maldonado (Uruguay), using participant observations, informal interviews, and field diary records. The objective was to analyze Uruguayan artistic gymnastics from the perspective of social and cultural studies of sport and feminisms, to understand the training process of gymnasts. In particular, it sought to identify how the regulatory structures of artistic gymnastics relate to bodily experience, showing that sports techniques, in their historical form of regulation, function as technologies of gender. The results indicate that the demands of artistic presentation in the women's discipline reinforce certain ideals of femininity, shaping corporealities and producing gymnasts who tend to construct a performance associated with the ideal of the woman-gymnast. Likewise, tensions were identified between institutional discourses and the practices of the athletes, with resistance and creative appropriations in the development of routines. It is concluded that artistic gymnastics techniques, far from being neutral, act as technologies of gender that shape both the bodily experiences and the identities of the gymnasts. This analysis allows for a problematization of the reproduction of heteronormative discourses in high-performance sports and, at the same time, makes visible possibilities for transformation in the field of gymnastics.
Keywords: sport; gender; artistic gymnastics; technique